2024
DOI: 10.1109/access.2024.3357396
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of FSO Communication System Under Rainy Weather Environment Using a Novel Encryption Technique

Somia A. Abd El-Mottaleb,
Amira G. Mohamed,
Hassan Yousif Ahmed
et al.

Abstract: Free Space Optics (FSO) has emerged as a viable solution to meet the growing demand for high bandwidth, secure data transmission, and high speed. However, the FSO system is highly susceptible to environmental factors, with precipitation in particular having a significant impact on FSO links. Optical loss, phase fluctuation, and multipath fading of the received optical power are all caused by these external factors. From this perspective, to improve the system's performance in such conditions, a novel image enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is observed that increasing the observation length can reduce the effect of any non-homogeneous smog patches inside the chamber. A small change in the density of aerosols can cause a significant change in the value of β γ as given by Equation (6). Two different approaches are used to characterize the smog attenuation, (i) based on different levels of visibility and (ii) different values of operating wavelengths, i.e., 780 nm and 1550 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that increasing the observation length can reduce the effect of any non-homogeneous smog patches inside the chamber. A small change in the density of aerosols can cause a significant change in the value of β γ as given by Equation (6). Two different approaches are used to characterize the smog attenuation, (i) based on different levels of visibility and (ii) different values of operating wavelengths, i.e., 780 nm and 1550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Atmospheric conditions such as fog, rain, and snow can affect the performance of FSO systems by causing signal attenuation [4,5]. However, using adaptive optics, tracking systems, and encryption techniques can help mitigate the effects of atmospheric attenuation [6,7]. FSO is a rapidly developing technology with the potential to revolutionize the way we communicate.…”
Section: Introductionmentioning
confidence: 99%